PENGARUH TESTOSTERONE REPLACEMENT THERAPY TERHADAP PROFIL LIPID DAN LEMAK PADA TUBUH - Irawan, Angeline Aprilia; Kurniawan, Yukhi; Satriyasa, Bagus Komang; Widianti, I Gusti Ayu (E-Jurnal Medika Udayana, 2022)
translator Afrikaans Albanian - shqipe Arabic - ??????????? Armenian - ??????? Azerbaijani - az?rbaycanca Basque - euskara Belarusian - ?????????? Bengali - ????? Bulgarian - ????????? Catalan - català Chinese - ???????? Chinese - ?? (????) Croatian - hrvatski Czech - ?eština Danish - dansk Dutch - Nederlands English Esperanto - esperanto Estonian - eesti Filipino Finnish - suomi French - français Galician - galego Georgian - ??????? German - Deutsch Greek - ???????? Gujarati - ??????? Haitian Creole - kreyòl ayisyen Hebrew - ????????? Hindi - ?????? Hungarian - magyar Icelandic - íslenska Indonesian - Bahasa Indonesia Irish - Gaeilge Italian - italiano Japanese - ??? Kannada - ????? Korean - ??? Latin - Lingua Latina Latvian - latviešu Lithuanian - lietuvi? Macedonian - ?????????? Malay - Bahasa Melayu Maltese - Malti Norwegian - norsk Persian - ????????? Polish - polski Portuguese - português Romanian - român? Russian - ??????? Serbian - ?????? Slovak - sloven?ina Slovenian - slovenš?ina Spanish - español Swahili - Kiswahili Swedish - svenska Tamil - ????? Telugu - ?????? Thai - ??? Turkish - Türkçe Ukrainian - ?????????? Urdu - ???????? Vietnamese - Ti?ng Vi?t Welsh - Cymraeg Yiddish - ????? Double-click Select to translate After turning 40 years old, testosterone hormone in men will decrease, but some data regarding the effect of Testosterone Replacement Therapy (TRT) on cardiovascular safety is still controversial. The aim of this systematic review is to investigate the effect of TRT on lipid profile and body fat in men with Late-Onset Hypogonadism (LOH) which affects the incidence of cardiovascular disease. The literature search was performed on the database, such as PubMed and Wiley Online Library and also additional manual searches were performed on the reference list of related studies. The identified articles were selected according to the eligibility criteria. A total of four articles were used in this systematic review and the quality of the study was assessed using the Jadad score. From the four studies that is used, four study discussed the effect of TRT on lipid profiles and two studies discussed the effect of TRT on body fat. On the administration of testosterone gel 50mg/day, all lipid profiles improved after nine months of intervention. However, with IM testosterone after one year, the improvement was only partial. All studies discussing the effect of TRT on body fat showed uniform results, namely a decrease in fat percentage. The results obtained by the studies included in this systematic review suggest that TRT can improve lipid profiles and also decrease body fat in men with LOH.